Analysis of Tensile Strength the Fiber Bagasse Particles Board with Resin Adhesives - Nurdin, Hendri -; Fernanda, Yolli; Handayani, Meisuri (Universitas Negeri Padang, 2018)
Development of the material be in the form of Particles it is possible to do so it can be an alternative to wood. Particle board is an engineered material that utilizes waste bagasse after sugar cane extraction process as an amplifier and as an adhesive used resin. Particle boards that have been produced, generally using wood powder, while the use of wood has been limited and diminished due to difficulty getting it. So the need for development in engineering the main material particle board in the form of wood powder and replace it with waste bagasse. The particle board manufacturing process is carried out by forging (compacting) between the mixture of sugarcane pulp particles and the BQTN 157 Resin adhesive. Percentage of mixed usage 50: 50 based on the fraction of weight and volume. In obtaining the mechanical properties carried out by tensile testing. From this research, the average particle pull strength is 1.81 MPa, strain 13,52% and elasticity 0,013 GPa. In obtaining particle board as an engineering material that has good ability influenced many things such as particle (mesh) raw material, adhesive use, mixed composition, the process of forging. From the characteristics of the test results obtained so that the particle board of the bagasse with resin adhesive is very possible to replace the type of particle board made from raw wood powder.